Ethical Leadership in Intercollegiate Sport - Laura Burton; Jon Welty Peachey (University of Kansas Libraries, 2014)
Given the significant issues leaders face in the intercollegiate sport context, the need to lead ethically is paramount. This special issue, Ethical Leadership in Intercollegiate Sport, highlights the need for ethical leadership, explores enhancing ethical leadership and ethical decision-making, and examines ways to reduce unethical behavior within intercollegiate athletics. This introductory paper defines ethical leadership and identifies opportunities to better understand ethical leadership in the context of intercollegiate sport.